PTU-081A Initial experience of a nurse-led irritable bowel syndrome clinic. (17th June 2017) - Neilson, M; Caulfield, L; Morris, AJ; Gaya, D; Winter, J; Cahill, A; Lachlan, N; Stanley, AJ; Forrest, E; Gillespie, R; Barclay, S; Smith, LA
Abstract : Introduction: Irritable bowel syndrome (IBS) is a common indication for Gastroenterology referral. We launched a "one-stop" nurse-led clinic for the diagnosis and management of patients with suspected IBS. Method: With the assistance of a pump priming grant an IBS Clinical Nurse Specialist (CNS) was recruited and trained by the lead gastroenterologist and community dieticians. GP referrals of patients under 50y with symptoms consistent with IBS without "red flag" symptoms were identified as suitable to be assessed in the clinic. Three clinics per week were established with consultation times of 30 min per patient. A 'Suspected IBS Protocol' for investigation and management was followed. Data on the final diagnosis, management and re-referral rates were collected prospectively. Results: Initial analysis is of 18 months of the service. 389 patients were identified, 48 (12%) failed to attend. Of the 341 patients reviewed 252 (74%) were female and 89 (26%) male. Median age was 32. 67 patients (20%) required further investigation in the form of colonoscopy/flexible sigmoidoscopy/upper GI endoscopy The final diagnosis was IBS in 264 patients (77%); of which 153 (58%) had IBS-D; 61 (23%) had IBS-C; 46 (17%) had IBS-M and 4 (2%) had post infectious IBS. 52 (15%) of patients had alternative diagnosis made: functional abdominal pain 15 (4.4%); Helicobacter Pylori 7 (2.1%); chronic constipation 6 (1.8%); bile salt malabsorption 4 (1.2%), diverticulosis 3 (0.9%); Crohn's colitis 2 (0.6%); Colonic schistosomiasis 1 (0.3%); small bowel Crohn's 1 (0.3%); lactose intolerance 1 (0.3%); gastritis 1 (0.3%), ovarian carcinoma 1 (0.3%); renal carcinoma 1 (0.3%); lymphocytic colitis 1 (0.3%); functional dyspepsia 1 (0.3%); non-coeliac gluten intolerance 1 (0.3%); inappropriate vetting 3 (0.9%). Two (0.6%) patients symptoms had resolved completely prior to review and 1 (0.3%) patient refused consultation. 12 (3.5%) patients defaulted from colonoscopy and have an unclear final diagnosis, 9 (2.6%) of patients failed to supply a stool sample for faecal calprotectin analysis therefore have an unclear final diagnosis. Dietary and lifestyle advice was provided to all patients. Medications were suggested in 140 patients (41%). 4 (1.1%) patients are awaiting investigation. 4 patients (1.1%) have been referred back to the IBS clinic by GP with unresolved symptoms. Conclusion: The service has been successful in confirming the diagnosis of IBS in the majority of patients. Only a small number have needed referral back to the service. The advantages of this service are that patients see a specially trained individual with the expertise and time required to manage them and facilitate discharge back to primary care. Diverting these patients to a CNS clinic can help reduce waiting times for consultant clinics. Disclosure of Interest: None Declared